PELAKSANAAN PENGAWASAN SATUAN POLISI PAMONG PRAJA (SATPOL PP) TERHADAP PERATURAN DAERAH KABUPATEN INDRAGIRI HILIR TENTANG GERAKAN MASYARAKAT MAGHRIB MENGAJI DI KECAMATAN TEMBILAHAN - Putri Wahyuli; Raden Imam Al Hafis (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
In order to realize the vision of Indragiri Hilir regency, namely: "New Spirit Indragiri Hilir Towards a Prominent, Dignity and Bermarwah Regency" and to make the Indragiri Hilir Regency as Qori and Qoriah hull then Regent Indragiri Hilir issued Local Regulation No. 2 Year 2016 on Magrhib Community Movement . This effort was made to invite the Muslim community to re-fill the prosperous mushola, surau, langgar and mosque, especially for children, youth, youth, fathers and mothers in all walks of the Muslim community. The concept of theory that the author uses is Oversight. And the theory used is the theory of Manullang with a Variable of Supervision This research aims to determine the level of Implementation Supervision Satpol PP Unit Against Local Regulation Indragiri Hilir Regarding Maghrib People Movement Mengaji Indragiri Hilir regency, where the program Movement Maghrib Mengaji Society measured by 3 indicators are: Standard, Assessment, Improvement. The type of research located in the Office of Satuan Pamong Praja Police Unit of Indragiri Hilir Regency is a descriptive survey with qualitative research method, which is collecting data by way of direct meeting and interacting with people in the research area. The Key Informant namely Section Head of Supervision and Observation Satpol PP, religious leaders, and teachers of Ngaji, and Informants namely Community Leaders. Data analysis in this research is to search and arrange systematically data obtained from interviews, observation, and documentation, by organizing data into categories, describing into units, synthesizing, arranging into patterns, choosing which is important and which will be studied, and made conclusions. Based on this technical analysis the researchers assessed and concluded that the implementation of supervision of civil service police unit (Satpol PP) in Tembilahan sub-district should be optimized and more effective.